2000
DOI: 10.5271/sjweh.570
|View full text |Cite
|
Sign up to set email alerts
|

Nonmalignant mortality among workers in six Norwegian aluminum plants

Abstract: Objectives This study investigated the associations between exposure to fluorides and polycyclic aromatic hydrocarbons (PAH) and mortality from nonmalignant diseases among workers in the Norwegian primary aluminum industly. Methods Mortality among 10 857 men, employed for more than 3 years in 1 of 6 aluminum plants, was investigated from 1962 to 1996, giving 239 246 person-years during follow-up. A job-exposure matrix covering all 6 plants was used to estimate the individual exposure to total fluorides and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 17 publications
0
9
1
1
Order By: Relevance
“…By isolating CTPV exposure to these areas of the plant, the proportion of workers in the higher CTPV exposed jobs is greatly reduced compared to Söderberg smelters. In contrast, the cumulative fluoride exposure levels observed in this cohort were similar to the Norwegian smelter fluoride levels [11,12,15].…”
Section: Exposure Assessmentcontrasting
confidence: 49%
See 1 more Smart Citation
“…By isolating CTPV exposure to these areas of the plant, the proportion of workers in the higher CTPV exposed jobs is greatly reduced compared to Söderberg smelters. In contrast, the cumulative fluoride exposure levels observed in this cohort were similar to the Norwegian smelter fluoride levels [11,12,15].…”
Section: Exposure Assessmentcontrasting
confidence: 49%
“…In addition to lung and bladder cancer, exposures in Söderberg smelters have also been associated with nonHodgkin lymphoma and pancreatic, stomach and kidney cancers [9][10][11][12][13][14], and with other chronic diseases, including fluoride exposure with respiratory disease mortality [12,15] and CTPV exposure with chronic obstructive pulmonary disease mortality [13,14] and heart disease mortality [16,17]. However, these findings have not been consistent across studies.…”
Section: Introductionmentioning
confidence: 87%
“…In another Norwegian study, Romundstad et al20 investigated mortality from nonmalignant diseases among subjects who had been employed for 3 years or more in six Norwegian aluminum smelters (Table 3). Exposure data on total fluorides were available, and data on smoking habits were available in three of the plants.…”
Section: Methodsmentioning
confidence: 99%
“…Several subsequent studies have shown an association between exposure to potroom fumes and asthma-like symptoms as well as bronchial responsiveness (Kongerud and Samuelsen, 1991; Søyseth et al , 1994; Abramson et al , 2010). Moreover, some studies have shown an increased mortality from chronic obstructive disease among potroom workers (Rønneberg, 1995; Romundstad et al , 2000a,b; Gibbs et al , 2007; Gibbs and Sevigny, 2007). However, the results of lung cancer studies in the aluminum industry have been inconclusive (Armstrong et al , 1994; Romundstad et al , 2000a,b; Gibbs et al , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some studies have shown an increased mortality from chronic obstructive disease among potroom workers (Rønneberg, 1995; Romundstad et al , 2000a,b; Gibbs et al , 2007; Gibbs and Sevigny, 2007). However, the results of lung cancer studies in the aluminum industry have been inconclusive (Armstrong et al , 1994; Romundstad et al , 2000a,b; Gibbs et al , 2007). The association between bladder cancer and exposure to benzo(a)pyrene in primary aluminum plants is well accepted (Gibbs and Labrèche, 2014).…”
Section: Introductionmentioning
confidence: 99%